Analisis Penggunaan Energi pada Usaha Mikro, Kecil, dan Menengah (UMKM) - Supriatno Supriatno (CV. IRA PUBLISHING, 2022)
Electrical energy is an essential requirement for humans to perform all kinds of enterprises covering micro, small, medium and large enterprises. Efforts to utilize electrical energy efficiently is a wise action. The aims of the research is to analyze the use of electrical energy in a building that is used for micro enterprise. The research was conducted by collecting primary and secondary data in the observed building. The scope of research data includes the room areas, electrical energy consumption, level of lighting, temperature and humidity. The calculating results are compared with the standard data in the peraturan mentri energi dan sumber daya mineral no 13 tahun 2012. The results of the research show that only one room of building is in wasteful criteria. The lighting level has a difference between 18% to 79% below the standard. Air humidity in rooms equipped with air conditioning meets the standards, while the room temperatures are still higher than the standard temperature.